Gold Nanoparticles and g‐C3N4‐Intercalated Graphene Oxide Membrane for Recyclable Surface Enhanced Raman Scattering. (3rd July 2017) - Qu, Lulu; Wang, Na; Xu, Hui; Wang, Weipeng; Liu, Yang; Kuo, Lidia; Yadav, T. P.; Wu, Jingjie; Joyner, Jarin; Song, Yanhua; Li, Haitao; Lou, Jun; et al.
Abstract : Toxic organic pollutants in the aquatic environment cause severe threats to both humans and the global environment. Thus, the development of robust strategies for detection and removal of these organic pollutants is essential. For this purpose, a multifunctional and recyclable membrane by intercalating gold nanoparticles and graphitic carbon nitride into graphene oxide (GNPs/g‐C3 N4 /GO) is fabricated. The membranes exhibit not only superior surface enhanced Raman scattering (SERS) activity attributed to high preconcentration ability to analytes through π–π and electrostatic interactions, but also excellent catalytic activity due to the enhanced electron–hole separation efficiency. These outstanding properties allow the membrane to be used for highly sensitive detection of rhodamine 6G with a limit of detection of 5.0 × 10 −14 m and self‐cleaning by photocatalytic degradation of the adsorbed analytes into inorganic small molecules, thus achieving recyclable SERS application. Furthermore, the excellent SERS activity of the membrane is demonstrated by detection of 4‐chlorophenol at less than nanomolar level and no significant SERS or catalytic activity loss was observed when reusability is tested. These results suggest that the GNPs/g‐C3 N4 /GO membrane provides a new strategy for eliminating traditional, single‐use SERS substrates, and expands practical SERS application to simultaneous detection and removal of environmental pollutants. Abstract : A multifunctional membrane including superior surface enhanced Raman scattering (SERS) and photocatalytic activity by intercalating gold nanoparticles and graphic carbon nitride into graphene oxide nanosheets is developed. The membrane exhibits the extraordinary ability for use in removal, SERS detection, and degradation of organic pollutants, holding great promise for environmental pollutants removal and monitoring.